Crafting Brand Authenticity: The Case of Luxury Wines* - Beverland, Michael B. (Journal of Management Studies, 2005)
abstract Authenticity is one of the cornerstones of contemporary marketing practice yet confusion surrounds the nature and use of authenticity in the brand arena. Examining the strategies of 26 luxury wine firms informs the authenticity of specific brands. Creating an impression of authenticity required creating a sincere story consisting of a creative blend of industrial and rhetorical attributes. Sincerity was achieved through the public avowal of hand crafted techniques, uniqueness, relationship to place, passion for wine production, and the simultaneous disavowal of commercial motives, rational production methods, and the use of modern marketing techniques. For the wineries, appearing authentic was critical in order to reinforce their status, command price premiums and ward off competitors. Images of authenticity were accomplished by developing a sincere story that enabled the firms to maintain quality and relevance while appearing above commercial considerations. This was achieved through the deliberate decoupling of their technical core from their espoused communications.